Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai Negeri Sipil Kantor Badan Strategi Kebijakan dalam Negeri Jakarta Pusat - Ikhwatul Sahra; Purwatiningsih (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
This study aims to analyze the influence of leadership style and work motivation on the performance of civil servants (PNS) at the Office of the Domestic Policy Strategy Agency (BSKDN) in Central Jakarta. The study employs a descriptive quantitative approach using a survey method, where data were collected through questionnaires distributed to a number of PNS within BSKDN. The collected data were then analyzed using multiple linear regression with the aid of statistical software to examine the relationships and effects between variables. The results indicate that leadership style has a substantial and positive effect on PNS performance, suggesting that effective, inspiring, and communicative leadership can enhance employee productivity and work quality. Moreover, work motivation also demonstrates a positive and significant impact on PNS performance, indicating that highly motivated employees exhibit greater dedication, discipline, and initiative in carrying out their duties. Further analysis shows that when leadership style and work motivation are applied simultaneously, both provide a substantial influence on improving PNS performance, emphasizing the importance of synergy between good leadership and employees’ internal motivation. The practical implications of this study underscore the urgency for BSKDN to develop leadership training programs that can inspire, motivate, and empower employees comprehensively. Additionally, designing sustainable strategies to enhance work motivation is also crucial to optimize the performance of all PNS within BSKDN, ensuring organizational goals are achieved effectively and efficiently. This study contributes to the development of human resource management practices in the government sector, particularly in the context of enhancing employee performance through the combination of effective leadership and optimal work motivation.